Coherent diffraction and cherenkov radiation in fibers - Naumenko G. A. Gennadiy Andreevich; Potylitsyn A. P. Alexander Petrovich; Bleko V.; Soboleva V. (2014, 2014)
The ability to use radiation of relativistic electrons in optical fibers in beam diagnostics was proposed by X. Artu at symposium RREPS-11. In this work the properties of different types of radiation induced in fibers by electromagnetic field of relativistic electron were considered. In this report we present the results of experimental investigation of this phenomenon in millimeter wavelength region for conditions of complete coherence. The nature and properties of radiation in fibers were analyzed experimentally for different geometry of fiber position with respect to the electron beam